Internações de crianças por condições sensíveis à atenção primária à saúde - Leôncio, Alane Barreto de Almeida (2020)
Introduction: Child health care, carried out since prenatal care, continues in childcare consultations, by monitoring child growth and development in Primary Care. At this level of care, it is possible to detect health problems early, with interventions carried out in a timely manner, reducing the risks of child morbidity and mortality. Therefore, the health care organization model that prioritizes the Family Health Strategy, tends to demonstrate improvement in the health conditions of the maternal and child population, especially of children under one year old, reflecting in the decrease in hospitalizations for diseases that, if treated properly and early, probably will not evolve to need for hospitalization. Objective: To analyze children's hospitalizations for conditions sensitive to care in Primary Health Care, in the State of Paraíba, and associated factors. Methodology: This is a descriptive, retrospective study, with secondary data from 311 medical records of children admitted to three reference pediatric hospital institutions in the State of Paraíba, from August 2017 to July 2018, using a quantitative approach. Data collection took place in March and April 2019, using an instrument containing a checklist to assist in the search for information. The statistical analyzes were processed in Software R, and analyzed using descriptive statistics, calculating the absolute and the relative frequency of the variables. In addition, some graphics were built on the Microsoft Office version 2010 spreadsheet. To verify the association between two variables, the chisquare test and Fisher's exact test were performed, considering a tolerable sample error of 5%. Logistic Regression was performed for data modeling. The data were presented by means of graphical representations and tables, and analyzed in the light of the relevant literature. The study was approved by the Research Ethics Committee, opinion number 3.159.523. Results: Respiratory and gastrointestinal diseases were considered the main causes of preventable hospitalizations of children under five years old in the state of Paraíba. Conclusion: The presence of hospitalizations for preventable conditions reflects possible failures in Primary Health Care, therefore, effective strategies are necessary to change the reality of care for children at this level of care.